Cyber-Culture Towards Information Technology Awareness in Indonesia - Heryono, Heri; Lisdayanti, Annisa (International Journal of Psychosocial Rehabilitation, 2020)
Recent technology involving humans as the central point of a prototypical agent has created an interdependence social life condition between them that might be emerging as a cultural bias. In Indonesia, people tend to use every technology off-handedly, and this condition impacts the integrated culture in a peristaltic way for every human aspect. Cyberculture popped out as the synthetic form of an old-fashioned culture followed before. It then becomes the most applicable terminology dealing with culture that is interfered with by technology. The terminology of information technology has been widely implemented almost in the whole activities of modern people. It becomes the main tool for doing jobs, living, and interacting. The ability to use and understand information technology also becomes a sign of awareness of technology. Then the use of this information technology turns out to be the new culture that people lived on it. Culture that requires people to update everything they are integrated in for their daily routine. The paper presents about cultural conditions related to information technology awareness in Indonesia.